Effects of dietary salt load and salt depletion on the course of hypertension and angiotensin II levels in male and female heterozygous Ren-2 transgenic rats - Husková, Zuzana; Kramer, Herbert J; Vaňourková, Zdeňka; Thumová, Monika; Malý, Jan; Opočenský, Martin; Škaroupková, Petra; Kolský, Alexander; Vernerová, Zdenka; Červenka, Luděk (Kidney & blood pressure research, 2007)
BACKGROUND: In the present study we evaluated plasma and kidney angiotensin II (ANG II) levels in female and male Ren-2 transgenic rats (TGR) in comparison to age-matched female and male normotensive Hannover Sprague-Dawley rats. METHODS: The rats were maintained on a normal sodium (NS) diet (0.6% NaCl) or fed a high sodium (HS) diet (2% NaCl) for 4 days or were sodium depleted by administration of 40 mg furosemide per liter drinking water overnight followed by 3 days of low sodium diet (0.01% NaCl) (LS + F). ANG II levels were determined by radioimmunoassay. RESULTS: Female TGR at the age of 38 days were already hypertensive and had developed cardiac hypertrophy, whereas male TGR at this age still exhibited a normotensive phenotype. HS diet increased the blood pressure (BP) but did not alter the ANG II levels in TGR at any age. LS + F decreased the BP without significant change in ANG II concentrations in TGR. Female TGR responded to salt loading and salt depletion by more pronounced changes in BP than male TGR. CONCLUSIONS: Female TGR develop hypertension more rapidly and the salt-sensitive component of hypertension is more pronounced in female than in male TGR. Copyright 2007 S. Karger AG, Basel.
Keywords: kuchyňská sůl; renin; geneticky modifikovaná zvířata; ledviny; Female; Angiotensin II; angiotensin II; financování organizované; Kidney; krysa rodu Rattus; Financing, Organized; zvířata; renální hypertenze; kardiomegalie; Renin; Cardiomegaly; Animals, Genetically Modified; potkani Sprague-Dawley; ženské pohlaví; krevní tlak; Hypertension, Renal; Male; Sodium Chloride, Dietary; Sex Characteristics; Heterozygote; pohlavní dimorfismus; Rats; Rats, Sprague-Dawley; Animals; heterozygot; Renin-Angiotensin System; mužské pohlaví; Blood Pressure; renin-angiotensin systém